SISTEM PENJUALAN BARANG PADA CV STAR DESIGN UNTUK BUSINESS TO BUSINESS BERBASIS WEB - Susanto, Susanto; Masithoh, Mauluddiah (STMIK Sinar Nusantara, 2024)
Sales Information System is an information system that provides information from several processes which include procurement, warehousing and reporting. Therefore, it is necessary to create an sales Information System application to improve company performance processes which were originally manual to be computerized which will produce more detailed reports. Making this application is done by means of data collection, system planning, system analysis, system design and Database . Making application programs developed with PHP . The Database used is MySQL and scripts are developed with Macromedia Dreamweaver. It can be concluded that the design and implementation of the Sales Information System at the CV Star Design is ready to be developed. The Inventory on this website uses the Business-to-Business. By logging into the website as a staff, the staff can fill in the required Inventory data and can fill in the data on goods sold and incoming goods from suppliers, all of which will later be entered into the Inventory Database . If all data has been processed, there will be an Inventory data menu where the data it contains the first entry date of the selected item to find out when the item entered so that when it is sold, the item sold is the oldest item. With the Business-to-Business method, the sales system will run sequentially thereby reducing the impact of damage from an item that is stored for too long in the storage of goods. In this web development using the Waterfall method and implemented using php and MySQL